ROLE OF CALL SALES IN IMPROVING LEVELSROOM DAYS IN THE SALER SALAK THE HERITAGEHOTEL - Paramitha, Laras; Priyanto, Priyanto (UI Scholars Hub, 2019)
The focus of this journal is about Role Sales Call to increase occupancy Hotel Salak The Heritage. The Purpose of this study is to know role sales call to increase occupancy and to describe obstacles of increase occupancy. This research is qualitative descriptive. The concept of this study is Tourism, Hotel, Marketing, Sales Call, SWOT analysis, Marketing Mix, Market Segmentation, Positioning, Deferensation. Stratgegy Marketing Hotel Salak The Heritage is Referring to Promotion. Marketing Strategy Salak The Heritage Hotel is important to increase occupancy every year.